(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Despite all the legal provisions, historically the statutory authorities have miserably failed to control the water pollution. How to bring down the extent of pollution to a desired level? This is really a problem. Especially when looked in the socio-economic spectrum. Our country is a developing country. We need industries to cater to the needs of our people, to enhance their standard of living and at the same time to compete with the advanced nations in the world market. The center of problem is of harmonization of pollution with industries.